2005
DOI: 10.1038/sj.bjc.6602613
|View full text |Cite
|
Sign up to set email alerts
|

The metastasis associated protein S100A4: role in tumour progression and metastasis

Abstract: The metastasis associated protein S100A4 is a small calcium binding protein that is associated with metastatic tumors and appears to be a molecular marker for clinical prognosis. Below we discuss its biochemical properties and possible cellular functions in metastasis including cell motility, invasion, apoptosis, angiogenesis and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(177 citation statements)
references
References 33 publications
5
168
0
2
Order By: Relevance
“…25 Many in vitro and in vivo studies in rodents have provided evidence that S100A4 is directly involved in tumor progression and metastasis. 25,26 Hence, the prognostic significance of S100A4 expression has been evaluated in various human cancers, and it has been shown to be a prognostic marker in breast, pancreatic, prostate, gallbladder, esophageal, gastric and non-small cell lung cancers. 27 With regard to thyroid cancer, S100A4 was reported to be the most highly expressed gene in a thyroid carcinoma cell line with high metastatic potential, and its overexpression was observed in most advanced thyroid carcinomas including papillary thyroid carcinomas and anaplastic carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…25 Many in vitro and in vivo studies in rodents have provided evidence that S100A4 is directly involved in tumor progression and metastasis. 25,26 Hence, the prognostic significance of S100A4 expression has been evaluated in various human cancers, and it has been shown to be a prognostic marker in breast, pancreatic, prostate, gallbladder, esophageal, gastric and non-small cell lung cancers. 27 With regard to thyroid cancer, S100A4 was reported to be the most highly expressed gene in a thyroid carcinoma cell line with high metastatic potential, and its overexpression was observed in most advanced thyroid carcinomas including papillary thyroid carcinomas and anaplastic carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…These genes were also chosen based on recent studies which suggest the role of S100 proteins in mediating various cellular processes including cell growth, differentiation, cell migration, and cell adhesion (20)(21)(22). Among S100 proteins, S100A4, S100A8, and S100A9 have emerged as potential prognostic markers for poor patient survival and metastasis of a number of cancers (14,(23)(24)(25). S100A8 and S100A9 were shown to be overexpressed in gastric cancer (26,27), prostate cancer (28), breast cancer (29), lung adenocarcinomas (30), pulmonary adenocarcinoma (30), and hepatocellular carcinoma (31).…”
Section: Discussionmentioning
confidence: 99%
“…Because mounting evidence suggested oncogenic activities of S100 proteins in the regulation of cell motility and invasion during human cancer progression and metastasis (14,15), the subsequent study focused on these two proteins. In order to ensure the real-time PCR data of S100A8 and S100A9 obtained by TaqMan assay, the SYBRGreen assay was done on these two genes and the same results were obtained (data not shown).…”
Section: Validation Of Microarray Analysis By Real-time Pcr and Revermentioning
confidence: 99%
“…S100A4 or metastasin, which is a member of the S100 family of calcium-binding proteins, has been shown to have an important role in breast cancer progression (Helfman et al, 2005;Garrett Regulation of NFAT5 by ddx5/ddx17 S Germann et al et al, 2006). We have recently reported that lipocalin 2 (LCN2), which also plays a role in breast cancer progression (Yang et al, 2009;Leng et al, 2011), is regulated by NFAT transcriptional factors (Fougere et al, 2010).…”
Section: Nfat5 Ddx17mentioning
confidence: 99%